Advanced blends as avisable extended option for thermal engines: emissions and performance on a Diesel Engine - Molina-Ramírez, Sergio; Cortés-Reyes, Marina; Herrera-Delgado, María Concepción; Auñón-Hidalgo, Juan Antonio; Larrubia-Vargas, María Ángeles; Alemany-Arrebola, Luis José (My University, 2022)
The stricter emission regulation for the automobile sector to achieve reduction in pollution that caused GHG in the atmosphere, have resulted in the search of alternative clean fuels which satisfy the demand of this sector. In this context, the incorporation of bio-based oxygenated compounds can be considered as an alternative to both, contribute to the decarbonisation of the energetic system and to reduce the fossil fuel dependence. A significant interest has been growing in long-chain additive alcohols as ternary Biodiesel-Petrodiesel-Oxigenated blends [1, 2], and indeed, bio-butanol has attracted interest as oxygenated compound because of its closer properties to the fossil-sourced fuels [3]. This contribution focuses on the study and development of different optimized Biodiesel-Petrodiesel- (bio)Butanol ternary advanced fuel blends and their performance on the different engine parameters and gas-emissions in a real diesel engine.
Keywords: Motores diesel; Petrodiesel; Butanol; Biodiesel blends; Diesel engines; Emissions